The Effectiveness of Picture Book Storytelling Methods in Improving Children's Speaking Skills - Hartini, Sri; Arianti, Rita; Zulmi, Fadhli; Amul Husni Fadhlan; Aslamiah Nasution, Soibatul; Ardesi Pratiwi, Rani (Al-Kahfi: Jurnal Pendidikan Agama Islam, 2025)
The main problem in this study is how good the children's speaking ability is before using the picture book storytelling method, how good the children's speaking ability is after using the picture book storytelling method and how effective the picture book storytelling method is on the speaking ability of group B children in RA IB IV Mahakarya, Luhak Nan Duo District, West Pasaman Regency. This study uses a quantitative approach, namely the pretest and posttest control group design. The population of the researcher is all children in RA IB IV Mahakarya, totaling 40 children and the sampling technique is simple random sampling, namely children in group B1, totaling 40 children. The data collection technique used is observation/observation then the data that has been obtained through different test analysis (t-test). Based on the results of the data analysis, it was obtained that the pret-test of the control class obtained a score of 416 with an average value of 20.8 in the MB category, the post-test of the control class obtained a score of 516 with an average value of 25.8 in the BSH category. Meanwhile, the pre-test experimental class score obtained 603 with an average value of 30.15 in the BSH category, in the post-test experimental class with a score of 661 with an average value of 33.05 in the BSB category. By obtaining these results there is an increase in children's speaking ability with the picture book storytelling method. We can see through the results from before when given the action and after being given the following implementation/treatment (20.81), implementation (12), implementation (14), implementation (14) and seen the value of the t table with a level of 5% seen from the t table gets a value of 2.08 then it can be seen that (t0) is greater than tt (5.44 > 2.08) therefore t0 is greater than tt then it can be said that Ha is accepted and Ho is rejected. This means that the picture book storytelling method can improve children's speaking ability at RA Islam Bakti IV Mahakarya, Luhak Nan Duo District, West Pasaman Regency